Penguatan Kapasitas Kader Petani dalam Penanganan Gigitan Ular Berbisa di Wilayah Antirogo - Maysaroh, Salma; Toni, Arya Adib; Sasongko, Nathasya Alfisyahr; Yunanto, Rismawan Adi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Venomous snakebites represent a significant health problem in agricultural areas, particularly in Antirogo Village, Jember Regency. Insufficient knowledge and skills in preventing and managing venomous snakebites increase the risk for farmers in this area. The Saung Tani Cekatan program aims to enhance the knowledge and preparedness of CEKATAN cadres in handling venomous snakebites. This program involves 30 CEKATAN cadres who receive training through educational methods using mobile applications and PowerPoint presentations, as well as demonstration methods. The activities were conducted in Antirogo Village, Jember Regency. The evaluation was carried out using pretest and posttest questionnaires consisting of closed-ended questions regarding the prevention and management of snakebites. The results showed an increase in the percentage of respondents who answered questions correctly: question 1 (53.3%), question 2 (76.6%), question 3 (86.6%), question 4 (66.6%), question 5 (70%), question 6 (83.3%), question 7 (90%), question 8 (96.6%), question 9 (96.6%), question 10 (100%), question 11 (96.6%), question 12 (100%), question 13 (90%), question 14 (100%), question 15 (56.6%), and question 16 (90%). In conclusion, the Saung Tani Cekatan empowerment program effectively increases cadre knowledge regarding preparedness and management of venomous snakebites in the Antirogo area. This program can be expanded to other agricultural sectors using similar methods.